Sistem Informasi Pengolahan Data Peserta Didik Baru Pada SMK Al Qolam Kota Agung - Andriani, Dwi; Renaldo, Riki; Amsir, Rojani (JELTec (Journal of Learning Technology), 2024)
Agung is still carried out manually, which often leads to issues such as delays in data processing, data duplication, and difficulty in retrieving information. This research aims to design and develop an information system for managing new student data to improve the efficiency and accuracy of data processing. The system is developed using the System Development Life Cycle (SDLC) methodology with the waterfall model, consisting of planning, analysis, design, implementation, and maintenance phases. The result of this research is a web-based information system that enables the admissions committee to manage prospective student data in a structured and systematic manner. The system enhances data input speed, minimizes errors, and provides real-time information. The implementation of this system is expected to make the new student admission process at SMK Al Qolam more effective and efficient